Renal Function Status in Patients with Diabetes Mellitus Having Diabetic Foot Infection and Role of Antibiotics: Renal Function Status in Patients with Diabetes Mellitus - Hussain, Shabab; Arrham, .; Javeriya Saeed, Syeda; Murtaza Anwar, Ahmad; Khan, Asif; Brohi, Saifullah (Pakistan Journal of Health Sciences, 2022)
It has been shown that antibiotic therapy in diabetic foot ulcers has a toxic effect on renal function. Objective: To assess the renal function among patients with diabetes mellitus having diabetic foot infection. Methods: It was a cross-sectional retrospective study in the surgical Unit of DHQ Teaching Hospital KDA Kohat for six-month duration from January 2022 to June 2022. 130 patients with diabetic foot ulcers were selected for this study. The patients receiving antibiotic with a low renal toxicity risk were included in Group-A and patients receiving antibiotics with an increased renal toxicity risk were included in group B. GFR was calculated and measured from Cockcroft-Gault equation and serum creatinine levels. SPSS 20.0 was applied for data analysis with paired t-tests, t-test and chi-square tests. Results: In group A there were 65 (50%) participants and 65 (50%) in group B. GFR after and before antibiotic therapy was 58.30±31.13 cm3 / min and 65.98±35.76 cm3 / min (p = 0.004), correspondingly. The GFR in group B was reduced significantly after antibiotic therapy (p = 0.003). Conclusions: Conferring to this study, renal function decreased and nephrotoxicity was noted after antibiotic treatment, the percentage of decline in GFR being greater in patients who received higher nephrotoxic antibiotics.